Semiotics in landscape design - Karsten Jorgensen (Landscape Review, 1997)
This paper claims that concepts of language can help us create better and more relevant landscape design. It is based on research undertaken by Karsten Jørgensen (1989), and subsequent studies carried out at the department of Land Use and Landscape Planning at the Agricultural University in Norway. The 'signs' that constitute the design language are categorised using the analytical vocabulary of landscape design; for example, elements, materials, effects and shapes. Studies of these signs are based on elements of semiotics and cognitive science, especially the Umwelt-theories developed by Jakob von Uexküll (Hoffmeyer 1994). We are constantly exposed to numerous signs of different kinds. Everywhere in society we see signs around us; for example, traffic signs, advertising signs and logos. It is therefore relevant to introduce the term 'semiosphere' in order to focus on the significance of semiosis at all levels of activity in the world, from cellular activities, to complex systems of development such as those found in a population. This study focuses on the semantic aspects of landscape architecture. In explaining the meaning of a statement, it is useful to have a set of rules or 'codes' to correlate a specific expression with a specific interpretation. These codes may be based on conventions, or on similarity between or stylisation of objects, such as natural or cultural landscapes. In any case, they are based on the interpreter's language and 'mind-structure'. At a general level, it is only possible to study sign content. To analyse meaning in landscape design you have to look at the context; for example, the overall composition of a garden or park and the situation, which includes the interpreter's cultural background, their experiences and so on. In other words, you have to analyse a specific case to be able to speak reasonably about meaning in landscape (de)signs.